Supply-demand matrix: a process-oriented approach for data warehouses with constellation schemas - Cavique, Luís (2020)
Star schema in data warehouses is a very well-established model. However, the increasing number of star schemas creating large constellations schemas add new challenges in the organizations. In this document, we intend to make a contribution in the technical architecture of data warehouses with constellation schemas using an extension of the bus matrix. The proposed supply-demand matrix details the raw data from the original databases, describes the constellation schemas with different dimensions and establishes the information demand requirements.